IMPACT OF INSURGENCY ON AGRICULTURAL PRODUCT DISTRIBUTION AND MARKETTING IN NIGER STATE, NIGERIA - Ajiboye, A.O.; Folagbade, A.M.; Oduleye, O.O.; Onah, C.C.; Amoh, M.U.; Ayankunle, K.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
Over the years, some parts of Niger State in Nigeria have been plagued with frequent attacks by insurgents. Among the areas affected is Shiroro Local Government Area (LGA). This study therefore seeks to assess the effects of insurgency on agricultural product distribution and marketing in Niger State with emphasis on Shiroro LGA. The study employed the survey research design while data were collected from the registered farmers, traders and transporters within the 15 wards of Shiroro LGA. A sample size of 400 was determined using the Taro Yamane formula and all the structured questionnaires were administered to the respondents within the study area using stratified random sampling technique. The collected data were then analysed using descriptive statistics like frequency, percentage and mean while Z-test statistics was adopted to test the hypothesis at 0.05 level of significance. Result from the study revealed that the insurgency resulted in low productivity from the farmers who are always on the run and thereby leading to increase cost of labour for the few that are around to work on the farms as well as increased on other farm inputs due to increase in transportation cost while there were reduction in supply and demand for farm product. The study shows that the Z-Cal value of 0.032 is less than the critical value of 0.05. The null hypothesis is therefore accepted and the alternate hypothesis is rejected. This therefore implies that there is no statistically significant difference between the mean responses of farmers and traders on the effects of insurgency on the profitability of farm products in Shiroro LGA. The study conclude that insurgency has negatively affected agricultural productivity, its transportation, distribution and marketing in the study area. It was then recommended that the Niger state government should endeavour to curb the issue of insecurity by exploring all possible means while also making farm inputs such as fertilizers, improved seeds, machinery, and herbicides readily available and accessible at subsidised prices in order to improve productivity.